Prepronociceptin-Expressing Neurons in the Bed Nucleus of the Stria Terminalis Signal Escape Behavior - Maria M. Ortiz-Juza; Randall L. Ung; Sophia M. Hegel; Ayden L. Ring; Noah W. Miller; Ruben A. Garcia-Reyes; Hiroshi Nomura; Hiroyuki K. Kato; Nicolas C. Pégard; Jose Rodriguez-Romaguera (Biological Psychiatry Global Open Science)
Background: Dysregulation in neural circuits that encode arousal responses to aversive stimuli is thought to contribute to changes in motivated behaviors associated with neuropsychiatric disorders. However, the relationship between arousal and motivation remains poorly understood. We previously identified that prepronociceptin-expressing neurons in the bed nucleus of the stria terminalis (PnocBNST neurons) modulate rapid physiological arousal responses to a motivationally salient aversive odor. However, whether PnocBNST neurons also signal behavioral actions triggered by an aversive odor is still unknown. Methods: In this study, we investigated the role of PnocBNST neurons in signaling behavioral responses to an aversive odor. We leveraged miniaturized head-mounted microscopes to monitor the calcium activity of PnocBNST neurons in vivo while freely behaving mice performed an odor preference test. Results: We found that the bulk activity of PnocBNST neurons increased as mice approached an aversive odor. Single-cell analyses revealed heterogeneity in response dynamics within the PnocBNST neuronal population upon initial exposure to the odor. Subsequent analysis revealed that the response dynamics of PnocBNST neurons that showed excitation when mice were in close proximity to the aversive odor were due to the initiation of darting away from the odor. Conclusions: These results highlight a novel role of PnocBNST neurons to signal escape behavior in response to an aversive stimulus. This, in combination with our previous findings that PnocBNST neurons encode arousal responses, supports a neurobiological relationship of arousal and motivation within extended amygdala circuits.